Prinsip-Prinsip Komunikasi dalam Bimbingan Pra Nikah (Studi terhadap Calon Pengantin di Kecamatan Ulee Kareng Kota Banda Aceh) - Rosmiati Rosmiati (Ar-Raniry: International Journal of Islamic Studies, 2019)
Communication is a medium for humans to interact each other. Communication is also a very basic need in daily life. An important point in communication is the extent to which messages can be received from the communicator to the communicant. To be able to make good communication must meet the principles and principles of communication. In essence, communication is carried out in a variety of human activities, both in ordinary non-formal activities and formalities, both in formal events and not, including communication carried out in the process of implementing pre-marital guidance between the prince / advisor as a guest speaker with the bride and groom participants . The most common problem explored in this Thesis is the mechanism for implementing pre-marital guidance in the Office of Religious Affairs in Ulee Kareng District, Banda Aceh City, and the principles of communication used in its implementation. The research method used is qualitative with the type of field study research. Research data were analyzed by descriptive analysis. There are two research results. (1) The mechanism for the implementation of pre-marital guidance at the Ulee Kareng Religious Affairs Office in Banda Aceh City is covered in three mechanisms, namely: First, the schedule for the management of pre-marital guidance every Wednesday, starting at 08.30 WIB to 12.30 WIB, including rest periods. Second, mechanisms related to guidance material, namely material on fiqh munakahat, Implementation of family functions, psychology of marriage and family, handling family conflicts, and managing relations between the two parties. Third, the guidance method is lecture method (muḥāḍarah / public speaking) and discussion. (2) The principles of communication used are covered by six principles, namely the principles of sadīdā or true words, ma'rūfā or good words, layyinā or meek words, maisūrā or appropriate words, balīghā or good words the wise, and the principle of karīmā or noble words.